Regional Single Currency Effects on Bilateral Trade with the European Union - Joan Costa-i-Font (London School of Economics and Political Science (LSE), European Institute, 2010)
This paper empirically examines the regional effects of sharing a single currency on bilateral trade with other European Union partners. It takes advantage of a gravity specification of bilateral trade between 17 Spanish regions and 13 European countries over the period 1997-2004, which in turn allows accounting for two distinct definitions of a single currency depending on its temporal set up. That is, the "exchange rate volatility effect" (from exchange rate fixing in 1999) is distinguished from the so-called "common currency effect" (resulting from the issuing of a new currency in 2002). Findings are suggestive of a regional concentration of currency union effects in a few regions, namely those relatively more open to trade. Such effects on regional trade within Europe are found to fade away over time. Trade enhancing effects are found to vary range from 45% to 16%. When the "exchange rate volatility effect" was significant, the pure currency union effect was found to be almost negligible.
Keywords: O4; F4; F11; F33; 330; gravity models; trade flows; regional heterogeneity; monetary union